2020
DOI: 10.1177/0304375421989572
|View full text |Cite
|
Sign up to set email alerts
|

The Queer Art of Failed IR?

Abstract: What is missing from the debate about the “end of IR theory” or the rejection of the now infamous “isms”? Queer theory. Those who declare that IR theory is over and those who see it as making a comeback; those who reject the “isms” and those who champion them seem like they are on opposite sides of a very wide spectrum. This article argues, however, that all is not as it seems. Instead, the various “sides” of the debates about the futures of IR all take for granted a common set of understandings of what resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 97 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…The state of LGBTQ politics and queer IR is changing (Weber, 2014; Sjoberg, 2014; Wilcox, 2014; Barkin & Sjoberg, 2020). A 2010 survey on LGBT people and research in Politics and International Relations disciplines found that ‘LGBT issues are undeniably a part of the discipline’, with 27% of respondents reporting that they engaged with LGBT topics in their research to some extent (Novkov & Barclay, 2010: 100).…”
Section: Taking Queer Questions Seriously In Ir?mentioning
confidence: 99%
“…The state of LGBTQ politics and queer IR is changing (Weber, 2014; Sjoberg, 2014; Wilcox, 2014; Barkin & Sjoberg, 2020). A 2010 survey on LGBT people and research in Politics and International Relations disciplines found that ‘LGBT issues are undeniably a part of the discipline’, with 27% of respondents reporting that they engaged with LGBT topics in their research to some extent (Novkov & Barclay, 2010: 100).…”
Section: Taking Queer Questions Seriously In Ir?mentioning
confidence: 99%